Editorial: the microbiome, aspirin and colorectal cancer—authors' reply. Issue 11 (18th November 2020) - Prizment, Anna E.; Onyeaghala, Guillaume; Church, Timothy R.
Abstract : LINKED CONTENT This article is linked to Prizment et al and O'Grady & Quigley papers. To view these articles, visit https://doi.org/10.1111/apt.16013 and https://doi.org/10.1111/apt.16071